Action Research on Student Absenteeism in Virtual Learning: Causes and Interventions - Subedi, Kusum Raj; Subedi, Upendra; Subedi, Suprabha (Shaheed Smriti Journal, 2024)
This action research paper investigates the causes of student absenteeism in virtual learning environments and explores strategies to enhance student participation and improve learning outcomes. The study highlights various factors contributing to absenteeism, including health-related issues, household responsibilities, limited access to technology, and lack of motivation. Additionally, it examines the role of teacher effectiveness, digital literacy, and the overall challenges faced in online education. By using a combination of qualitative action research methods, the research aims to provide actionable solutions to mitigate absenteeism. The findings propose solutions such as improving technological access, enhancing teacher training in virtual education, fostering parental involvement, and developing engaging content to motivate students. The study ultimately seeks to enhance student learning experiences in the digital age and ensure higher engagement and academic success in virtual classrooms.